The impact of COVID-19 on development assistance - Brown, Stephen (Université d'Ottawa | University of Ottawa, 2021)
This article analyzes the impact of the COVID-19 pandemic on foreign aid. Using examples from Canadian foreign aid, it argues that, despite the terrible toll it is exacting, the crisis has accelerated some significant positive pre-existing trends, both by destabilizing the perception of aid as flowing essentially from the Global North to Global South and by reinforcing awareness of the importance of joint efforts for global public goods and humanitarian assistance, as well as debt relief. However, it has also reinforced potentially harmful self-interested justifications for aid, which could align assistance more with donors’ priorities than the needs of the poor. An important trend reversal is the renewed emphasis on well-being. Two other crucial trends remain unclear—the COVID-19 pandemic’s impact on multilateral approaches and on aid flows. How donors respond to the COVID-19 pandemic and its aftermath over the next few years will depend on their political will, and will profoundly shape the future of development co-operation.
Keywords: foreign aid; umanitarian assistance; poverty; Canada; COVID-19